The history of Alma-Ata Conference - Tejada de Rivero, David A. (2018)
The historical account of the International Conference on Primary Health Care of Alma-Ata (Soviet Union) WHO/UNICEF, the most important international health policy event in the early 70’s that marked a milestone in public health in the world, is presented. It was attended by 134 countries, 67 international organizations and many non-governmental organizations. Unfortunately, China was the big absentee. At the end of the historical account, the Declaration of Alma-Ata 1978 is presented.